Soluble PD-L1 as a novel biomarker predicts poor outcomes and disease progression in de novo myelodysplastic syndromes - Xingcheng Yang; Lijun Jiang; Xiaoying Zhang; Juan Peng; Hu Qian; Lifang Huang; Shaolong He; Zhiqiong Wang; Liting Chen; Yicheng Zhang; Ling Ma; Yuan Chen; et al. (BMC, 2024)
Abstract The role of the compromised immune microenvironment, including immune checkpoints, in myelodysplastic syndromes (MDS) has been identified as critical This study aimed to investigate the expression patterns of immune checkpoints, particularly soluble PD-1/PD-L1 (sPD-1/sPD-L1) as well as PD-1 on effector T cell subsets, and assess their prognostic value and potential regulatory roles in MDS. 161 MDS patients were enrolled, including 129 patients were primarily diagnosed with de novo MDS, together with 59 MDS patients who underwent hypomethylating agents (HMAs) therapy. Plasma sPD-L1 level was elevated in newly diagnosed MDS patients, which was also found to be associated with MDS disease progression that further increase in higher IPSS-R score group. Patients with increased sPD-L1 expression at diagnosis exhibited notably poorer overall survival, and multivariate Cox analysis indicated that elevated sPD-L1 was an independent risk factor. Furthermore, the levels of multiple cytokines and membrane-bound PD-1 on T cells were found to correlate with sPD-1/sPD-L1 levels in plasma. Importantly, we also found sPD-L1 levels significantly increased in MDS patients who showed progression of disease following HMAs therapy. In conclusion, we found elevated plasma sPD-L1 levels in MDS patients are associated with disease progression and poorer overall survival. This study showed that sPD-L1 is a potential biomarker for prognosis and a target for immunotherapy in MDS.